dx/2xz=dy/2yz=dz/z^2-x^2-y^2
"\\frac{dx}{2xz}=\\frac{dy}{2yz}=\\frac{dz}{z^2-x^2-y^2}"
The first equation gives
"\\frac{dx}{x}=\\frac{dy}{y}", i.e. "\\frac{xdy-ydx}{xy}=\\frac{x}{y}d(\\frac{y}{x})=0",
"d(\\frac{y}{x})=0"
"\\frac{y}{x}=k={\\rm const}"
The second equation gives
"\\frac{dx}{x}=\\frac{2zdz}{z^2-x^2-y^2}=\\frac{dz^2}{z^2-(1+k^2)x^2}"
"xdz^2-(z^2-(1+k^2)x^2)dx=0"
"\\frac{xdz^2-z^2dx}{x^2}-(1+k^2)dx=0"
"d(\\frac{z^2}{x}-(1+k^2)x)=0"
"\\frac{z^2}{x}-(1+k^2)x=C"
"z^2-(1+k^2)x^2=Cx"
"z^2-x^2-y^2=Cx"
The general integral surface of the given ODE has an equation determined by an arbitrary differentiable function "\\Phi" of "(k,C)" :
"\\Phi(k,C)=\\Phi(\\frac{y}{x},\\frac{z^2-x^2-y^2}{x})=0"
Answer. "\\Phi(\\frac{y}{x},\\frac{z^2-x^2-y^2}{x})=0", where "\\Phi" is an arbitrary differentiable function.
Comments
Leave a comment